2022
DOI: 10.1371/journal.pone.0279291
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of under-registration of chronic kidney disease stages 3–5 in Belgian general practices using logistic regression

Abstract: Background Early detection and treatment of chronic kidney disease (CKD) can prevent further deterioration and complications. Previous studies suggested that the diagnosis is often made when advanced renal failure occurs. The aims of this study were to describe the prevalence of unregistered CKD stages 3–5 in a Belgian General Practitioner population, to determine risk factors for under-registration and to investigate the diagnostic delay. Methods The analyses were carried out in the INTEGO database, a Fland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…Our previous research showed that there were small differences between registered and non-registered patients at baseline. 15 Hypertension was more frequently present in the registered (64.4% of the registered population) compared with the non-registered (51.7% of the non-registered population). Similar results were found for type 2 diabetes (33.1%) of the registered compared with 28.2% of the non-registered).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Our previous research showed that there were small differences between registered and non-registered patients at baseline. 15 Hypertension was more frequently present in the registered (64.4% of the registered population) compared with the non-registered (51.7% of the non-registered population). Similar results were found for type 2 diabetes (33.1%) of the registered compared with 28.2% of the non-registered).…”
Section: Discussionmentioning
confidence: 91%
“…We need to consider the effect of antihypertensive medication on this outcome, since 48% of the patients took an ACE-I or an ARB. 15 The beneficial effect of these drugs on cardiovascular events and all-cause mortality has been confirmed in the past. 37 Ettehad et al described that in patients with CKD, smaller risk reductions in cardiovascular events were seen as a result of antihypertensive medication than in patients without CKD.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations